2013
DOI: 10.1111/dsu.12336
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of and Patient Satisfaction with Injectable Hyaluronic Acid with 0.3% Lidocaine Hydrochloride for the Treatment of Superficial Perioral Lines or Superficial Lateral Canthal Lines

Abstract: Injectable HA with a particle size of 350 μm was efficacious and resulted in high patient improvement scores in improving moderate to severe superficial, vertical perioral lines and superficial, horizontal, lateral canthal lines. Three of the 40 enrolled patients demonstrated granuloma formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 14 publications
2
4
0
Order By: Relevance
“…In this study, all patients were willing to repeat the treatment and to recommend it to friends/family. This corroborates the findings of several publications that show good patient outcomes, immediate results, and high satisfaction when using HA fillers for treatment of lines and wrinkles 16 , 17 and for volume restoration. 6 , 18 …”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In this study, all patients were willing to repeat the treatment and to recommend it to friends/family. This corroborates the findings of several publications that show good patient outcomes, immediate results, and high satisfaction when using HA fillers for treatment of lines and wrinkles 16 , 17 and for volume restoration. 6 , 18 …”
Section: Discussionsupporting
confidence: 91%
“…The overall range of mean improvement for all treated areas (1.08–1.76) was similar to the improvements reported on a 5-point scale in the literature: mean improvement of 1.6 points for perioral lines, 16 1.5 for NLF, 3 1.9 for deep lines and wrinkles, 9 and 1.5 for infraorbital hollow. 12 No published data on the mean improvement for marionette lines, which was the second most common indication in this study (n=41, 38%), with similar products were found.…”
Section: Discussionsupporting
confidence: 83%
“…12 One should be cognizant, although, that gels with a higher G′ can cause visible small blue papules or nodules (Tyndall effect) if injected superficially in the skin. 17,18 In contrast, in areas that are more static or with superficial wrinkles, resistance to deformation by muscle movement is less critical and gels with lower G′ are better utilized. These gels are also better suited for areas that need more softness, such as the lips.…”
Section: Hyaluronic Acid Derivativesmentioning
confidence: 99%
“…11,23 Restylane, in contrast, can be injected superficially given its smaller particle size, although like all HA fillers, Restylane does create Tyndall effect in standard concentrations when used in the papillary dermis. 11,17 Overall, both Restylane and Perlane have a higher G′, hence are more firm with less spreading of product and is therefore better suited for placement in the subdermal level, particularly in the midface. 20 In a real-time ultrasound study, Micheels et al demonstrated that Restylane, with its high viscosity and least tendency to spread, was distributed fairly evenly in welldefined boluses within the deep reticular dermis.…”
Section: Hyaluronic Acid Derivativesmentioning
confidence: 99%
“…Filler injections growth rate is about the same for patients regardless the gender [1]. Key features of filler treatment rely on patient compliance and satisfaction rate [2][3][4][5][6], generally measured through satisfaction questionnaires [7], and safety, efficacy and lasting effect of the corrections [8].…”
Section: Introductionmentioning
confidence: 99%